University celebrates diversity at Commencement events - Uribes, Tom::::::::: (2013)
The honorable Hilda Solis, former Secretary of Labor under President Barack Obama and a former U.S. Congresswoman, will be honored during Fresno State's 37th Annual Latino Commencement Celebration.